The Anti-Inflammatory Effects and Molecular Mechanism of Citri Reticulatae Pericarpium Essential Oil: A Combined GC-MS and Network Pharmacology Study - Junmei Pu; Jiabao Cui; Hui Yang; Jianxin Cao; Shanshan Xiao; Guiguang Cheng (Foods)
This study investigated the chemical composition and anti-inflammatory effects of essential oils extracted from Citrus aurantium flower, Citrus sinensis, Brazilian Citrus sinensis, Citrus limon, Citrus bergamia, and Citri Reticulatae Pericarpium using steam distillation and gas chromatography-mass spectrometry (GC-MS). Their anti-inflammatory activities were assessed in LPS-stimulated RAW 264.7 cells. Among them, Citri Reticulatae Pericarpium essential oil (CRPEO) exhibited the most potent anti-inflammatory effects, with D-Limonene (76.51%), α-Pinene (2.68%), and Linalool (2.11%) as its primary constituents. The CCK-8 assay showed that the essential oil exhibited no cytotoxicity on HaCaT cells at a concentration of 50 μg/mL. CRPEO significantly preserved cell viability and reduced the production of pro-inflammatory mediators, including tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-1β, and nitric oxide (NO). Gene expression analysis via RT-qPCR further confirmed the downregulation of TNF-α, IL-6, IL-1β, and inducible nitric oxide synthase (iNOS) at the mRNA level. Network pharmacology and molecular docking studies were employed to identify α-Bulnesene as a key bioactive component of CRPEO and revealed that its principal target is the NLR Family Pyrin Domain-Containing 3 (NLRP3) inflammasome. These findings highlight the strong anti-inflammatory potential of CRPEO and suggest its promising therapeutic application for inflammation-related conditions.